2022
DOI: 10.1038/s41598-021-04325-1
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing is a highly reliable method to analyze exon 7 deletion of survival motor neuron 1 (SMN1) gene

Abstract: Spinal muscular atrophy (SMA) is one of the most common and severe genetic diseases. SMA carrier screening is an effective way to identify couples at risk of having affected children. Next-generation sequencing (NGS)-based expanded carrier screening could detect SMN1 gene copy number without extra experiment and with high cost performance. However, its performance has not been fully evaluated. Here we conducted a systematic comparative study to evaluate the performance of three common methods. 478 samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…A broad range of options is needed to help diagnose SMA prenatally. The gold standard for SMA diagnosis is multiplex ligation probe analysis [ 26 ], a targeted test. However, as an increased NT thickness is not currently considered a sign of SMA, this would not have been employed in the case described here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A broad range of options is needed to help diagnose SMA prenatally. The gold standard for SMA diagnosis is multiplex ligation probe analysis [ 26 ], a targeted test. However, as an increased NT thickness is not currently considered a sign of SMA, this would not have been employed in the case described here.…”
Section: Discussionmentioning
confidence: 99%
“…If the signs are not clear, then prenatally the best next-generation sequencing method is exome sequencing; however, it requires specific bioinformatic analysis [ 27 ], as SMN1 and SMN2 are genes with high homology. If a neuromuscular disorder is suspected, then targeted neuromuscular disease panels can be used, as described by Zhao et al and Tan et al [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, novel bioinformatic tools will allow structural variations detection based on sequencing data increasing ECS sensitivity [ 38 ]. In this context, a very recent publication by Zhao et al reported the validation of NGS for the detection of SMN1 gene copy numbers by analyzing 478 samples with multiplex ligation probe amplification (MLPA), real-time quantitative polymerase chain reaction (qPCR), and NGS; interestingly, they found that NGS performed better than the other two methods and suggested that it can be useful in ECS context to reduce the need for multiple methodologies and, in turn, analysis time and costs [ 39 ].…”
Section: Expanded Carrier Screening: Definition Pros and Consmentioning
confidence: 99%
“…Nonetheless, a study by Zhao S.et al revealed that the NGS approach has the lowest number of retests with 100% speci city, sensitivity, and accuracy; however, the primary drawback of this method is too costly. The most used technique for SMA detection is q-PCR, which offers excellent performance at a reasonable price with above 95% sensitivity (Zhao S, 2022). In this study, we used the Intelligence Ratio method which is based on qPCR.…”
Section: Introductionmentioning
confidence: 99%